FEASIBILITY STUDY ON THE DEVELOPMENT OF INTEGRATED SOLID WASTE TREATMENT FACILITY (TPST) IN SITIREJO MALANG, INDONESIA - Hardianto Hardianto; I Nyoman Sudiasa; Mikhael Valerius Seran (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2020)
Sitirejo Malang TPST in its implementation can reduce the high generation of solid waste at the source. Existing solid waste management is only for non composted solid waste. Therefore there is a need for research on the generation, composition and characteristics of solid waste related to the feasibility of developing TPST service areas. The data used in this study include primary data such as generation, composition, and characteristics of solid waste, solid waste processing stages, and solid waste treatment facilities. Secondary data such as TPST service areas, TPST operational and financial technical data. Calculation of solid waste generation using the method of load-count analysis, calculation of the composition of solid waste using the quarterly method, calculation of physical characteristics include the specific gravity of solid waste. In the calculation of financial analysis, the economic criteria used are Net Present Value (NPV), while the feasibility of development uses several development scenarios. The results showed that the treated solid waste were 10.73 m3/day, while the weight reached 1,071.17 kg/day. The composition of composted solid waste consists of yard waste of 31.32% and food waste of 31.18%. The composition of non composted solid waste reaches an average of 0.24% - 13.18%. The average density of garbage in collecting vehicles is 100.51 kg/m3. The results of the financial analysis show that the projection until 2028 of 32.5 m3/day shows a value of NPV>0, thus TPST activities are considered feasible, both the existing and development scenarios.